Late Triassic adakite‐like volcanic rocks in Moguqi area in the central Great Xing'an Range, NE China: Implications for partial melting of delaminated thickened crust. (15th June 2017) - Xu, Jiulei; Zheng, Changqing; Shi, Lu; Xu, Xuechun; Han, Xiaomeng; Li, Juan; Cui, Fanghua
Abstract : Adakite‐like volcanic rocks in the Moguqi area of the central Great Xing'an Range of NE China consist of trachyandesites and trachydacites. These rocks yield LA–ICP–MS U–Pb zircon ages of 229.5–232.6 Ma. These adakite‐like rocks are high in Sr (459–1960 ppm) and MgO (1.2–4.3%), low in Y (11.4–23.70 ppm) and Yb (0.88–2.07 ppm), and have high Sr/Y ratios (37.17–146.31) and high Mg# values (0.43–0.58). These characteristics are similar to those of rocks derived from slab melting. However, the existence of Early Triassic stable continental sedimentary rocks of the Laolongtou Formation does not favour this mode of formation. The zircon εHf(t) values of the samples range from +8.09 to +13.29, indicating the primary magmas were generated by partial melting of juvenile crust. Analysis of geophysical data, combined with the previously published history of the Hegenshan–Heihe Suture in this region and the southward subduction of Mongol–Okhotsk oceanic plate, suggests that the Late Triassic adakite‐like volcanic rocks in the Xing'an Massif formed from the partial melting of delaminated thickened crust in an extensional setting. This occurred after orogenesis involving the Xing'an Massif and the Songnen Massif and was influenced by southward subduction of the Mongol–Okhotsk oceanic plate.